An insight into zolpidem abuse and dependence - Kinga Świąder; Ewa Szymańska; Sandra Ostaszewska; Kinga Augustynowicz; Jakub Chrzanowski; Jan Łoginoff; Przemysław Morawski; Zuzanna Popińska; Filip Pactwa (Kazimierz Wielki University, 2023)
Background: Z-drugs (zopiclone, zaleplon, and zolpidem) are commonly prescribed medicine classes associated with a risk of abuse, dependence or withdrawal.   Objective: The purpose of our work is to review the current knowledge on the evidence for z-drugs harms and estimate the prevalence of dispensed prescriptions.  Material and Methods: A literature review was conducted in PubMed database using the key words: "Zolpidem", "Z-drugs", "Abuse", "Dependence"  Results: According to our findings, zolpidem should be prescribed with the same caution as BZDs, especially in patients with a history of drug abuse or in the elderly.  Conclusion: Psychiatrists and physicians should be aware of the misuse potential of zolpidem and adopt measures restricting its use.